A Decomposition Analysis of Inequality in Malnutrition among under Five Children in Iran: Findings from Multiple Indicator Demographic and Health Survey, 2010 - Abdollah ALMASIAN KIA; Sahar GOODARZI; Heshmatollah ASADI; Ardeshir KHOSRAVI; Aziz REZAPOUR (Iranian Journal of Public Health, 2019)
Background: Nutritional status at the early stages of children’s lives is essential for growth and development not only in infancy but also in adult life. This study aimed to measure the inequality in malnutrition among under-five children in Iran and explore the impact of socioeconomic factors on this inequality using a regression-based decomposition approach.